Biochemical analysis of new type mutants of japonica rice that accumulate water‐soluble α‐glucans in the endosperm but retain full starch debranching enzyme activities. (12th August 2016) - Nakagami, Tsuyoshi; Yoshihara, Hiroki; Nakamura, Tetsuhiro; Utsumi, Yoshinori; Sawada, Takayuki; Fujita, Naoko; Satoh, Hikaru; Nakamura, Yasunori
Abstract : Amylopectin has a highly regulated branched structure called cluster structure, which causes the glucan to be hydrophobic and to form a semicrystalline architecture of starch granules. It is known that lesions of the isoamylase1 ( ISA1 ) gene result in accumulation of a water‐soluble glucan (WSG) called phytoglycogen instead of amylopectin in various plant species. This type of cereal mutant is referred to as sugary‐1 and accumulates a large amount of phytoglycogen in the endosperm. In this study, another WSG‐synthesizing mutant has been isolated from japonica rice. This mutant accumulated a significant amount of WSG in the center of endosperm. No significant changes were found in activities of ISA and pullulanase and in the compositions of ISA1 homomer and ISA1‐ISA2 heteromer. In addition, activities of starch branching enzyme and starch synthase isoforms were not altered. The accumulated WSG had a specific fine structure, that differed from that of phytoglycogen. Thus, we designated this new mutant as the sugary‐2 mutant. Our study results strongly suggest that the Sugary‐2 gene product plays an important role in amylopectin synthesis of rice endosperm and identifies a new factor that controls the normal amylopectin structure, especially at the early developmental stage of the endosperm.